The value of quantitative fluorescence polymerase chain reaction for the products of conception in the era of copy number variation sequencing - Yang, Shaozhe; Zhang, Hewei; Wang, Yongli; Zhang, Qingwei; Wu, Yongyong; Fu, Xiuhong; Li, Rongxiang (Frontiers in Genetics, 2026)
PurposeThe purpose of this research was to assess the effectiveness of copy number variation sequencing (CNV-Seq) and quantitative fluorescence polymerase chain reaction (QF-PCR) in detecting chromosomal abnormalities in products of conception of women and to evaluate the pros and cons of three different combined detection strategies, CNV-Seq and QF-PCR.MethodsGenetic testing was conducted on 701 samples using QF-PCR and CNV-Seq. The detection efficiency of the two methods for various chromosomal abnormalities was calculated. The relationships between maternal age, miscarriage gestational age, number of prior miscarriages, and conception method with fetal chromosomal abnormalities were assessed. The detection efficiency and cost of three different combined detection strategies were compared.ResultsMaternal cell contamination was found in 2.57% of samples. The overall occurrence rate of various chromosomal abnormalities was as high as 67.20% (459/683). QF-PCR was effective in detecting maternal cell contamination, triploidy, and common aneuploidies but was not effective in detecting mosaicism. Advanced maternal age, abnormal pregnancy history, early abortion, and naturally conceived products of conception were more likely to detect aneuploidy but were unrelated to triploidy and CNVs.ConclusionQF-PCR can effectively complement the limitations of CNV-Seq. Employing QF-PCR to rule out maternal cell contamination prior to performing CNV-Seq on all samples is the best detection strategy.